THERAPY OF FIBRINOUS PLASTIC ANTERIOR UVEITIS - A. L. Onishchenko; A. V. Kolbasko; A. D. Tchernyshev (Oftalʹmologiâ, 2015)
Aim. To analyze the efficacy of modified pupillary massage technique using cycloplegic agent Appamide Plus in the treatment of anterior uveitis. Patients and methods. 45 patients (25 men and 20 women) aged 21‑69 with endogenous uveitis (51 eyes) were enrolled in the study. Etiology of uveitis was identified in 57.7 % of cases: herpes simplex virus (22.2 %); systemic disorders — rheumatoid arthritis, Reiter syndrome, Bechterew’s disease, psoriasis (17.7 %); local infection — purulent periodontitis or sinusitis (11 %). Patients were divided into two groups. Group I received basic therapy in combination with traditional pupillary massage. Group II received basic therapy in combination with modified pupillary massage using Appamide Plus (muscarinic receptor antagonist and alpha adrenergic agonist) and plasma exchange with cell mass ozonation. Results. Inflammation of the uveal tract was prevented in all patients. In group I (traditional pupil massage), posterior synechiae persisted in 26 % of cases. In group II (pupil massage using Appamide Plus), anterior chamber humor was transparent, posterior synechiae were broken, normal pupillary response was re-established. Additionally, inflammatory exudate in the anterior chamber and endothelial precipitates resolved by 3.3 days earlier than in group I (р < 0.05). Visual outcomes were also better in Appamide Plus group. T cell-mediated immunity study revealed initial CD3+ cell and T cell subpopulation deficiency. Relative and absolute references of T cells and their subpopulations tended to decrease even when uveitis signs reduced. Conclusions. T cell-mediated immunity depression is probably due to pharmacotherapy. Appamide Plus eye drops are highly effective for therapeutic mydriasis and pupillary massage in the course of anterior uveitis treatment to prevent synechiae formation in enlarged or small pupil.